Hardiness and Resilience in Women Who have Spontaneous Abortions - Hana Pratiwi Putri; Arthur Huwae (Faculty of Psychology, Universitas Semarang, 2023)
Women who experience spontaneous abortion result in various psychological impacts. To overcome this, they must have a hardiness that can help individuals become strong and resilient in the face of complex events to survive and become resilient. This study aims to examine the relationship between hardiness and resilience in women who experience spontaneous abortion. The research method used is quantitative correlation design. Participants in this study were 117 women who had spontaneous abortions using the accidental sampling technique. The measuring instruments in this study used the Hardiness scales (α = 0.857) and Adult Resilience Scale (α = 0.920). The correlation test results showed a significant positive relationship between hardiness and resilience (r = 0.256 and sig. = 0.003), indicating that hardiness is one of the factors that has a relationship with strength. The higher the hardiness, the higher the resilience in the life of women who have experienced spontaneous abortion. The character of hardiness must continue to be formed by getting used to the dynamics of every challenge that exists to help individuals be resilient to face every difficult period in life.Keywords: Hardiness, resilience, woman, spontaneous abortion.